Adoption of Improved Late Sown Mustard Cultivation Practices in Bihar - Sunita Kushwah , Sushil Kumar; A. K.Singh (Indian Journal of Extension Education, 2016)
Mustard contributes around 23.2 per cent of total oilseed production in India. Attempts are being made to improve productivity and to increase area under mustard by adoption of HYVs (High yielding varieties). In order to compare conventional mustard with HVY, 65 front line demonstrations were carried out. The demonstrations resulted enhancement in productivity. The yield was found to be increased from 7 (q/ha) in local check to 11 (q/ha) in FLDs. Similarly, the benefit: cost ratio can be further improved to 2.92 as compared to 1.6 in local check. Lack of market and support price (93.47) were recorded major constraints in late sown mustard cultivation. Hence increase in yield over farmer’s practices was evident which indicated the need of educating farmers through front line demonstration.